Sociological, approach to gender and socioeconomic inequalities - Mušić Lejla (Theoretical Hypotheses and Empirical Results, 2025)
Inequalities speak to, all inclusive, most created impediments to the practicing the Human rights and uniformity. Acquittal Worldwide Reports, WUNRN [1] reports, Worldwide dangers reports appear that there are complex shapes of human flotsam and jetsam, in the modern. Social imbalances speak to unequal openings interior the society, based on the race, gender, and race. Human rights [2] activists, together with the environmental rights activists, and the activists for the rights of the minorities, (coloured, vagrants, and war veterans, 1970-ties had begun campaign, all inclusive, against the persecution and the segregation. Giddens in Humanism, underscores the deconstruction of sex based imbalances that saturate private and open circle, similarly. World Wellbeing Association, characterises the financial disparities as the most complex and risky, for the future: “Socioeconomic imbalances, related to wage, work, instruction, as well as statistic contrasts, such as age or sexual orientation, are related with unequal presentation to natural chance variables. They contribute to the wellbeing disparities and most regularly put impeded bunches at essentially higher hazard for the natural wellbeing effects” [4]. The primary speculation of this examination is that the social disparities are rising each day, and that the way better joint technique of diverse science systems, particularly sociologists, NGO-s, Women’s organisations for help offer assistance in their diminishment. Key terms:migrants, gender, race, social inequalities/ financial disparities , financial disparity